2009
DOI: 10.1177/1541344610385753
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking, Transformative Learning, Sustainable Education, and Problem-Based Learning in Universities

Abstract: In universities, the need for education associated with sustainability is widely accepted and it is increasingly being introduced. However, the associated concepts and terms are contested—education for sustainable development and education for sustainability represent increasing levels of change required in curricula, while achieving sustainable education will require even greater change. A transformative pedagogy underlies and contributes to the extent of the change, as more argue for a range of analytical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
201
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(245 citation statements)
references
References 14 publications
(14 reference statements)
1
201
0
19
Order By: Relevance
“…Critical pedagogy has been explored mainly through the post formal educational thinking which champions education which emancipates the thinking of the unrepresented [3], [22]. This includes gender, religion, Eastern culture as well different abilities in challenged individuals which remain unaddressed in an education system which is mainly colonial, Western, abled and male.…”
Section: What Is Liberatory Pedagogy?mentioning
confidence: 99%
See 1 more Smart Citation
“…Critical pedagogy has been explored mainly through the post formal educational thinking which champions education which emancipates the thinking of the unrepresented [3], [22]. This includes gender, religion, Eastern culture as well different abilities in challenged individuals which remain unaddressed in an education system which is mainly colonial, Western, abled and male.…”
Section: What Is Liberatory Pedagogy?mentioning
confidence: 99%
“…Engineering education and sustainable development (SD) are linked by many pedagogies which has brought possibilities for development of young engineers to acknowledge the agenda as imperative for engineering and society in the future [1]- [3]. These pedagogies have been highlighted in its benefit in bringing understanding of concepts, practice and values in relation to SD which stems from the educational efforts within Educational research undertaken particularly, from Environmental Education and Education for Sustainable Development (ESD) [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…The notion of transdisciplinarity represents a higher-order learning towards increased ecological consciousness and an integrative practice Baffording a deeply relational sense of what it is to be human at this most challenging of times^(p. 217). This view is shared by Thomas (2009) and Adomßent (2013), the latter arguing that transdisciplinarity has been established on the university level as a comparatively new participative form of scientific practice and culture concerning involvement with sustainability. Similarly, Colucci- Gray et al (2013) claimed that transdisciplinarity is essential for the articulation of and dialogue between different forms of knowledge in academia.…”
Section: Education For Sustainabilitymentioning
confidence: 99%
“…ESD's emphasis on political actions and changed values, attitudes and new ways of thinking-and especially critical thinking as advocated by Sterling 2014, Thomas (2009, Upadhyay (2005), Jickling and Wals (2008) and others-raises an urgent question: If the main problem is not the lack of knowledge, of new sets of values or of appropriate ways of thinking, but rather decreased sensibility towards our coalescing with nature, how do we revitalize such a competency? Colucci- Gray and Camino (2016) noted that embodied experiences and practical work are vital elements of sustainability education.…”
Section: Education For Sustainabilitymentioning
confidence: 99%
“…According to Jennings 15 as a result of the PBL experience, students can link theory to practice, deal with complexity of a particular situation, or improve judgment, expertise, and enliven teaching. PBL activities promoting the development of five important abilities in students: getting knowledge faster and value it, because it is used to solve real problems; awakens in them the importance of developing skills for solving real life problems; learn by themselves, since they require to find and evaluate information from several sources; explain complicated concepts in simple words, since they are obtaining meaningful through a real life problem definition; and work professionally in an interdisciplinary group in a collaborative way 16 . Previous works have demonstrated that students' insights of their learning experience are clearly related with the inclusion of PBL activities into the course.…”
Section: Problem Based-learning Origins and Benefitsmentioning
confidence: 99%